The effect of sacrificing the posterior cruciate ligament on total knee arthroplasty with cruciate retaining highly congruent rotating platform prosthesis - Long Chen; Jie Xu; Yuan Lin; Fen Qi Luo; Yu Guo Yu (Journal of Orthopaedic Surgery and Research, 2021)
Abstract Objective To analyze the effect of sacrificing the posterior cruciate ligament (PCL) on the early postoperative outcome of cruciate retaining (CR) highly congruent rotating platform TKA. Methods From May 2018 to September 2019, 105 cases of total knee arthroplasty (TKA) with CR highly congruent rotating platform prosthesis were retrospectively analyzed. According to the tension of posterior cruciate ligament, they were divided into sacrifice group (29 cases, 27.6%) and retention group (76 cases, 72.4%). Preoperative and postoperative The Hospital for Special Surgery (HSS) score, range of motion (ROM) were compared between the two groups. In addition, postoperative infection, prosthesis loosening, bearing dislocation, and other complications were also compared. Results All patients were followed up for 11~24 months (mean 18.14 ± 3.52) months. There was no significant difference in general data, preoperative HSS score, and ROM between the two groups (P > 0.05). At the last follow-up, HSS score and ROM of the two groups were better than those before operation (P < 0.05). However, there was no significant difference between the two groups (P > 0.05). Moreover, there were no complications such as infection, loosening of prosthesis, and bearing dislocation in all cases. Conclusion In CR, highly congruent rotating platform TKA with or without tension of the PCL can achieve satisfactory outcomes. Tension-free PCL do not cause joint instability.